Investigation of Functional Difference between TecIII and TecIV in Mammals COS-1 Cells Using GFP Fusion Proteins - Atmosukarto, Ines I. C.; Booker, Grant W, (Annales Bogorienses, 2005)
Signal transduction cascades are critical components of intra-and inter-cellular communication. Key component of such cascades includes tyrosine kinases. One such family of tyrosine kinase is the Tec family of tyrosine kinases. This family of tyrosine kinases is expressed mainly in cells of the hematopoietic lineage, and mutations in at least one of its one member of this family, Btk, has so far been associated with the human immunodeficiency disorder X-Linked Agammaglobulinemia. Two major isoforms of the Tec transcript, referred to as TecIII and TecIV have been detected in various mouse embryonic and adult tissues, as well as in a number of different hematopoietic cell lines: TecIV is the full length Tec protein with functional PH, TH, SH3, SH2, and Kinase domains, while TecIII is gen rated by the splicing out of exon 8 sequences to yield a shorter peptide with a non-functional SH3 domain. Using GFP-TecIII fusion proteins, this shorter isoform of Tec was shown to have biological characteristics that differed from TecIV.